Qishen Yiqi alleviates periostin-mediated cardiac fibrosis and hypertrophy in Dahl hypertensive rat hearts and angiotensin II-induced cardiac organoids - Fan, Siwen; Du, Hongxia; Li, Siyu; Xiao, Guangxu; Zhao, Yuhan; He, Shuang; Fan, Guanwei; Zhu, Yan (Frontiers in Pharmacology, 2025)
BackgroundArterial hypertension is a significant risk factor for cardiovascular health. Long-lasting hypertension leads to damage to multiple organs, such as the heart, kidneys, and vascular bed damage. We have previously shown that a component-based Chinese medicine Qishen Yiqi (QSYQ) lowered the blood pressure and ameliorated kidney damage in salt-sensitive hypertensive rats. However, its effect on the hypertensive rat heart remains unknown. This study aims to explore the efficacy and mechanism of QSYQ in hypertensive heart disease.MethodsDahl salt-sensitive hypertension rats were fed with normal or high-salt diets with gavage administration of QSYQ or control drug for 9 weeks. Cardiac ultrasound, tissue pathology and transcriptome analysis were performed on the hypertensive heart in vivo. A cardiac spheroid model we established previously was treated with angiotensin II to mimic a hypertensive heart in vitro.ResultsQSYQ prevented the development of diastolic dysfunction of LVPW and E/A and reduced fibrosis and hypertrophy in the hypertensive rat hearts. In cardiac spheroids, angiotensin II induced an exacerbated hypertrophic morphology, fibrotic pathology, and elevated collagen expression. QSYQ treatment effectively reversed these abnormalities. Transcriptome analysis revealed that periostin is a key target of QSYQ in the hypertensive heart. Consistently, QSYQ also significantly downregulated the expression of periostin and fibrosis indicators such as TGF-β, α-SMA, Col1a1 and Col3a1.ConclusionQSYQ alleviates cardiac fibrosis and hypertrophy in Dahl Salt-sensitive hypertension rats in vivo and angiotensin II-induced cardiac organoids in vitro via regulating multiple signaling pathway activator periostin.